(Liquid plus liquid) equilibria of polymer-salt aqueous two-phase systems for laccase partitioning: UCON 50-HB-5100 with potassium citrate and (sodium or potassium) formate at 23 degrees C - Estela Lladosa (2012)
Aqueous two-phase systems (ATPS) are recognized as very suitable techniques for the recovery of target solutes in biological applications. Three new phase diagrams of (UCON 50-HB-5100 + potassium citrate + water), (UCON 50-HB-5100 + sodium formate + water), and (UCON 50-HB-5100 + potassium formate + water) systems were measured at 23 degrees C. The binodal curves were successfully described using the empirical equation suggested by Merchuk and co-workers. The reliability of the tie-line data experimentally determined was evaluated using the equations reported by Othmer-Tobias and Bancroft and satisfactory linearity was obtained for all ATPS. Among the salts studied, potassium citrate proved to be the most effective in ATPS formation, providing the largest heterogeneous region. Besides, the effect of both anions and cations in the size of the heterogeneous region and in the slope of the tie-lines has been compared. For the same salts and conditions, the heterogeneous region using UCON as the phase-forming polymer is larger than using polyethylene glycol. Furthermore, laccase partition in the UCON-salt ATPS was studied and it was found that in all cases enzyme partition occurred preferably to the bottom phase (salt-rich phase). Laccase concentration in the salt-rich phase was approximately 2-fold that in the top phase, thus UCON-salt ATPS can be a suitable biphasic system for laccase extraction.